Using Potential Accessibility Measure for Urban Public Transportation Planning: A Case Study of Denizli, Turkey - Gorkem Gulhan; Huseyin Ceylan; Ozgur Baskan; Halim Ceylan (Promet - Traffic&Transportation, 2014)
Policy makers and planners evaluate the implementation of the urban public transport (UPT) planning studies in terms of some objective measures such as load factor, mean volume per trip, capacity usage ratio and total capacity. In some cases, improving these measures may lead an unforeseen decrease on accessibility to the opportunities in terms of UPT users. Thus, this study aims to evaluate Potential Accessibility (PA) as an efficiency measure in decision stage of UPT planning. It widely depends on fieldwork, surveys, data inventories and existing plans. In this context, a comprehensive UPT planning has been carried out through VISUM traffic simulation software by taking the PA into account, and a four-step UPT planning procedure has been proposed. The results showed that PA may alternatively be used as an evaluation instrument in decision stage of UPT planning while the objective measures are insufficient to represent the effectiveness of alternative scenarios.